Nanostructured Mesoporous Titanium Dioxide Thin Film Prepared by Sol-Gel Method for Dye-Sensitized Solar Cell. (23rd May 2011) - Liu, Yu-Chang; Lu, Yun-Fang; Zeng, Yz-Zhen; Liao, Chi-Hung; Chung, Jen-Chieh; Wei, Tsong-Yang
Abstract : Titanium dioxide (TiO2 ) paste was prepared by sol-gel and hydrothermal method with various precursors. Nanostructured mesoporous TiO2 thin-film back electrode was fabricated from the nanoparticle colloidal paste, and its performance was compared with that made of commercial P25 TiO2 . The best performance was demonstrated by the DSSC having a 16 μ m-thick TTIP-TiO2 back electrode, which gave a solar energy conversion efficiency of 6.03%. The ability of stong adhesion on ITO conducting glass substrate and the high surface area are considered important characteristics of TiO2 thin film. The results show that a thin film with good adhesion can be made from the prepared colloidal paste as a result of alleviating the possibility of electron transfer loss. One can control the colloidal particle size from sol-gel method. Therefore, by optimizing the preparation conditions, TiO2 paste with nanoparticle and narrow diameter distribution was obtained.